Kajian Pesan-Pesan Dakwah dalam Cerita Rakyat 'Ande-Ande Lumut' pada Buku Karya Arti Purbani - Septy Anggrainy (Pawarta: Journal of Communication and Da'wah, 2025)
Da’wah, as a means of conveying Islamic teachings, must adapt to the developments of the times. No longer limited to face-to-face interaction, da’wah can now be delivered through various media, one of which is print media. Da’wah bil qolam, or written da’wah, serves as an effective alternative for communicating religious messages. Books are a powerful medium for this purpose, as seen in the folk tale “Ande-Ande Lumut” by Arti Purbani. This study aims to analyze the content of da’wah messages found within the story. A significant background of this research is the declining reading interest among children, driven largely by the rapid advancement of digital technology. Children today are more inclined to engage with gadgets and online games than to develop literacy through reading. This research is qualitative in nature, using a content analysis approach and categorized as library research. The primary data source is the story of “Ande-Ande Lumut” from Arti Purbani’s book, while secondary sources include books, academic journals, scholarly articles, and relevant online resources. Data collection methods involved literature review, reading, and note-taking. The findings indicate that the folk tale contains a range of da’wah messages, including messages of aqidah (faith in Allah and destiny), sharia (worship and social transactions), and akhlaq (morality towards God and fellow humans). Among all the paragraphs, sharia messages are the most dominant, followed by akhlaq, and aqidah.